Communications - Time-Life Books (Alexandria, VA Time-Life Books, 1986)
Contents: The glimmer of electronic connections; Expanding horizons with networks; Fibers and waves to span the globe...
Includes bibliography and index
Keywords: Công nghệ thông tin